A new LiCoPO4 polymorph via low temperature synthesis - Jähne, Carsten; Neef, Christoph; Koo, Changhyun; Meyer, Hans-Peter; Klingeler, Rüdiger (Journal of materials chemistry. A, Materials for energy and sustainability, 2013)
Non-olivine LiCoPO4 microcrystals have been synthesized at low temperatures by microwave-assisted hydrothermal synthesis. The resulting octahedra-like micrometer-sized crystals exhibit a Pn21a symmetry and are isostructural to LiZnPO4. The orthorhombic lattice constants are a = 10.023(8) Å, b = 6.724(7) Å, and c = 4.963(4) Å. The microcrystals are metastable and transform to olivine LiCoPO4 upon heating above T ≈ 220 °C under an argon atmosphere. The magnetic properties confirm a phase pure material with a Co-valence of 2+, and imply long-range antiferromagnetic ordering below TN = 11 K. Electrochemical analysis by means of cyclic voltammetry displays a reversible redox couple at around 5.1 V/4.8 V vs. Li/Li+.
Gesehen am 24.03.2021
Im Titel ist die Zahl 4 tiefgestellt